HEPATITIS C VIRUS IN A POPULATION OF INFERTILE COUPLES - R. da Silveira, Themis (2022)
Objective: Hepatitis C virus transmission in assisted reproduction may pose a risk for the baby, technicians, and gametes or embryos from non-contaminated parents. This study aimed at determining the prevalence and risk factors for hepatitis C virus infection in a group of infertile couples.Methods: Four hundred and nine patients attending the infertility clinic at Hospital de Clínicas de Porto Alegre, Brazil, between 1997 and 1998, were screened for anti-HCV (ELISA) and HBsAg (ELFA). Hepatitis C virus (HCV) infection and semen viremia was also investigated using HCV RNA detection Results: All subjects were negative for HBV and HIV. The overall prevalence of anti-HCV was 3.2% (8/ 248) among women and 3.7% (6/161) among men. From the 14 HCV-positive patients, two were lost, and serum was collected from the remaining 12 patients for assessment of HCV RNA, resulting in five HCVpositive cases (one woman and four men). Only one of these positive cases had viremia levels > 500,000 RNA copies/ml. There was a significant risk association for being HCV-positive in women with HCV-positive male partners (P < 0.001). In male patients, the correlation between use of intravenous drugs and HCVpositivity was also significant (P < 0.001).Conclusions: Infertile patients should be screened before assisted reproductive technology (ART) procedures, since the risk for vertical and laboratory HCV infection is not well determined, and HCV prevalence is not negligible in this group.